Enhancing Organizational Agility through Effective Knowledge Management Practices: An Empirical Analysis (International Journal of Food and Nutritional Sciences, 2023)
This empirical analysis investigates the relationship between effective knowledgemanagement practices and organizational agility. Knowledge management, encompassingprocesses like knowledge creation, capture, storage, sharing, and application, has becomeincreasingly crucial for organizations in dynamic and competitive environments